Taxes and marriage: A two-sided search analysis - Hector Chade; Gustavo Ventura (The University of Western Ontario, Department of Economics, 2000)
This paper studies the effects of differential tax treatment toward married and single individuals in the US on marriage formation and composition, divorce and labor supply. We develop a marriage market model with search frictions and heterogeneous agents that is sufficiently rich to capture key elements of the problem under consideration. We then calibrate the model and use it to evaluate the quantitative effects of a number of tax reforms aimed at making the tax law neutral with respect to marital status. We find that reforms can have substantial effects on the labor supply of married females and on the degree of assortative mating.
Keywords: 330; Familienbesteuerung; Einkommensteuer; Suchtheorie; Arbeitsangebot; Steuerreform; Theorie; USA; Ehe